# Homework Help: Need Help

1. Jan 13, 2008

### Ejayrazz

Perchance someone here has some background in Philosophy, specifically symbolic logic? For the life of me I can't figure out the following:

A v D
(~B ^ ~C) = D
B => ~(C=> A)
~B

What I have so far is this:

1| A v D ............................P
2| (~B ^ ~C) = D .............P
3| B => ~(C =>A) ............P
4| |B ................................A
5| | |C .............................A
r| | |?
s| | |?
t| | |?
u| | |?
v| | |A ..............................1, ?-?, ?-?, vE
w| | C=>A ........................5-v, =>I
x| | B => ~(C =>A) ..........2, R
y| | ~(C =>A) ..................w, x, =>E
z| ~B ...............................4, w, y, ~I

What I can't figure out is how to get the disjunction elimination for A in the second sub-derivation. Anyone have a clue?

2. Jan 13, 2008

### Mystic998

I'm not sure about what you're doing as I have limited experience with this kind of thing, but as far as I can tell, if you assume B you get a contradiction:

B => C ^ ~A (equivalent to proposition 3)
~A => ~B ^ ~C (props 1 and 2)
So, you get B => C ^ ~C (or B => ~B...either way).

Or is that way off?